Efficacy and safety of tailin formulation combined with continuous low-dose antibiotic therapy in patients with recurrent urinary tract infection: A multicenter, randomized, controlled clinical trial - Li, Tonglu; Xu, Yingru; Yuan, Gang; Lu, Wen; Jian, Guihua; Gong, Xuezhong (Frontiers in Pharmacology, 2022)
Persistent inflammation associated with recurrent urinary tract infection (rUTI) is a crucial inducement of inflammation driven renal fibrosis (IDRF). Although continuous low-dose antibiotic therapy (CLAT) is the common treatment for rUTI, its clinical efficacy remains unsatisfactory. Tailin Formulation (TLF), a Chinese herbal formulation prescribed for treating rUTI, is effective in alleviating symptoms and reducing recurrence. This study was to evaluate the efficacy and safety of TLF combined with CLAT compared with CLAT used alone in patients with rUTI. In this multicenter, randomized, controlled clinical trial, patients were assigned (1:1) to receive either TLF+CLAT or CLAT for 12 weeks. The primary outcome was the efficiency rate at week 12 of the treatment. The second outcomes were the recurrent rate at week 4 and week 12 post treatment; the post-treatment changes in renal tubular function markers (urinary N-acetyl-β-d-glucosaminidase (NAG) and β2-microglobulin (β2-MG)), profibrotic factors (urinary Monocyte Chemoattractant Protein-1 (MCP-1) and Transforming Growth Factor beta1 (TGF-β1)) and traditional Chinese medicine (TCM) symptoms; vital signs indicators and serious adverse events (SAEs) were also be monitored throughout the trial. A total of 195 patients were included in the final analysis. TLF+CLAT group had higher efficient rate and lower recurrence rate compared with CLAT group (p<0.01). Significant decrease of urinary NAG and β2-MG were observed in TLF+CLAT group vs. CLAT group (p<0.01), similar changes were observed in profibrotic factors (urinary MCP-1 and TGF-β1) (p<0.05), which indicated that TLF might have potential renal tubular protection and anti-fibrosis effects. Additionally, positive correlation within a certain range was showed in correlation analysis of medical history (months) of rUTI patients with urinary MCP-1(r=0.50, p<0.05) and TGF-β1(r=0.78, p<0.01). Significant difference was also observed in TCM symptoms (p<0.01). There were no obvious adverse reactions occurred during this study. We conclude that TLF combined with CLAT was superior to CLAT used alone in reducing rUTI recurrence, alleviating the non-infection-related physical symptoms, protecting renal tubular and anti-fibrosis, which suggests this novel therapy might be an available treatment with great promise in treating rUTI.